2002
DOI: 10.1034/j.1398-9995.2002.23739.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a residual group in low‐molecular‐weight allergoids of Artemisia vulgaris pollen on their allergenicity, IgE‐ and IgG‐binding properties

Abstract: According to our results, all three modification procedures yielded allergoids with a similar extent of modification. No single biochemical parameter investigated in the study could predict the degree of reduced allergenicity in vivo. The most reduced allergenicity was seen in the succinyl derivative while the preservation of IgG binding epitopes was of the highest degree for the carbamyl derivative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…When these sera were used to load RBL cells, native extract as well as allergoid stimulated comparable mediator release from the basophil cells. These results regarding the native allergen-specific IgE are in accordance with results that show reduced allergenic activity of allergoids in vivo and in vitro [13, 14, 29], which confirms that some IgE epitopes might be altered or no longer directly accessible after modification. Allergoid production links allergens and non-allergenic proteins, thereby unpredictably changing the nature and distribution of IgE epitopes.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…When these sera were used to load RBL cells, native extract as well as allergoid stimulated comparable mediator release from the basophil cells. These results regarding the native allergen-specific IgE are in accordance with results that show reduced allergenic activity of allergoids in vivo and in vitro [13, 14, 29], which confirms that some IgE epitopes might be altered or no longer directly accessible after modification. Allergoid production links allergens and non-allergenic proteins, thereby unpredictably changing the nature and distribution of IgE epitopes.…”
Section: Discussionsupporting
confidence: 78%
“…These so-called allergoids have been in use for SIT for the last 30 years [8, 9, 10, 11, 12]. They are usually generated by incubating the native extracts in the presence of cross-linking agents like formaldehyde, glutaraldehyde or other substances reacting with ε-amino acids [13], which results in the formation of more or less large protein complexes. These complexes show a fundamentally reduced capacity to bind IgE [14, 15]depending on the size of the formed complexes, thereby minimizing the release of anaphylaxis-inducing mediators.…”
Section: Introductionmentioning
confidence: 99%
“…These reports all conclude that allergoids show reduced allergenicity in IgE binding and IgE inhibition assays, different basophil activation tests, or skin tests [10,13,14,15]. This was confirmed in the present study (fig.…”
Section: Discussionsupporting
confidence: 80%
“…Studies of allergoids have demonstrated reduced allergenicity by various in vitro methods as well as skin prick testing [10,13,14,15], and treatment with allergoids has shown efficacy in reducing symptom and medication scores in some studies [7, 8]. However, the clinical effect of allergoids may be compromised because they seem to lack the ability to modify allergen-specific T cell responses [12, 17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation